Association of Risk Factors and Comorbidities With Chronic Pain in the Elderly Population - Neil Mookerjee; Nicole Schmalbach; Gianna Antinori; Subhadra Thampi; Dylan Windle-Puente; Amy Gilligan; Ha Huy; Megha Andrews; Angela Sun; Roshni Gandhi; William Benedict; Austin Chang; et al. (SAGE Publishing, 2024)
Introduction/Objective: Chronic pain disorders affect about 20% of adults in the United States, and it disproportionately affects individuals living in the neighborhoods of extreme socioeconomic disadvantage. In many instances, chronic pain has been noted to arise from an aggregation of multiple risk factors and events. Therefore, it is of importance to recognize the modifiable risk factors. The aim of this study was to investigate the comorbid medical conditions and risk factors associated with chronic pain disorders in patients aged 65 years and older. Methods: Our team retrospectively reviewed medical records of elderly patients (65 years and older) who were evaluated in our outpatient medicine office between July 1, 2020 and June 30, 2021 for acute problems, management of chronic medical problems, or well visits. We divided our patients into a group who suffered from chronic pain disorder, and another group who did not have chronic pain disorder. The association of variables were compared between those groups. Results: Of the 2431 patients, 493 (20.3%) had a chronic pain disorder. A higher frequency of females in the group with chronic pain disorder was found compared to the group without a chronic pain disorder (60.6% vs 55.2%; P  = .033). The mean ages between the two groups were similar in the group with a chronic pain disorder compared to the group without (76.35 ± 7.5 year vs 76.81 ± 7.59 year; P  = .228). There were significant associations of certain comorbidities in the group with a chronic pain disorder compared to the group without a chronic pain disorder, such as depression (21.9% vs 15.2%; P  < .001), anxiety (27.0% vs 17.1%; P  < .001), chronic obstructive pulmonary disease (8.7% vs 6.1%; P  = .036), obstructive sleep apnea (16.8% vs 11.6%; P  = .002), gastroesophageal reflux disease (40.8% vs 29.0%; P  < .001), osteoarthritis (49.3% vs 26.1%; P  < .001), other rheumatologic diseases (24.9% vs 19.4%; P  = .006), and peripheral neuropathy (14.4% vs 5.3%; P  < .001). Conclusion: Female sex, depression, anxiety, chronic obstructive pulmonary disease, obstructive sleep apnea, gastroesophageal reflux disease, osteoarthritis, other rheumatologic diseases, and peripheral neuropathy were significantly associated with chronic pain disorder in elderly patients, while BMI was not associated with chronic pain disorder.